TREATMENT AND VACCINE PREVENTION OF ROTAVIRAL INFECTION AMONG CHILDREN - T.V. Kulichenko (Union of pediatricians of Russia, 2007)
Irrespective of the level of healthcare system development rotaviral infection is a serious medical, social and economic problem at all times. Any infant has to undergo rotaviral gastroenteritis. The run of the disease among infants is mostly often aggravated by dehydration and needs intense treatment of exicosis. The standard of treatment is an oral rehydration, which is in most cases contributes to a quicker improvement of the children's status. In the meantime, according to the metaphor put forward by the who experts «the best solution» to prevent acute rotaviral diarrhea today may become a rotaviral vaccine. Nowadays, in different countries of the world, two vaccines, which showed high efficiency and safety in clinical research, have been registered. Application of these vaccines may contribute to the significant reduction of the acute forms of rotaviral infection among infants, hospitalizations and mortality caused by rotaviral gastroenteritis. This article highlights the principles of treatment and possibility for vaccine prevention of rotaviral infection among children.Key words: rotaviral infection, gastroenteritis, diarrhea, children, rehydration, vaccine prevention, rotaviral vaccine.